The Role of Gut Microbial β-Glucuronidase in Estrogen Reactivation and Breast Cancer - Sui, Yue; Wu, Jianming; Chen, Jianping (Frontiers in Cell and Developmental Biology, 2021)
Over the past decade, the gut microbiota has received considerable attention for its interactions with the host. Microbial β-glucuronidase generated by this community has hence aroused concern for its biotransformation activity to a wide range of exogenous (foreign) and endogenous compounds. Lately, the role of gut microbial β-glucuronidase in the pathogenesis of breast cancer has been proposed for its estrogen reactivation activity. This is plausible considering that estrogen glucuronides are the primary products of estrogens’ hepatic phase II metabolism and are subject to β-glucuronidase-catalyzed hydrolysis in the gut via bile excretion. However, research in this field is still at its very preliminary stage. To speed up the process, this review outlines the biology of microbial β-glucuronidase in the gastrointestinal tract and elaborates on the clues to the existence of microbial β-glucuronidase - estrogen metabolism - breast cancer axis. The research gaps in this field will be discussed and possible strategies to address these challenges suggested.